Awareness of diabetes and diabetic retinopathy among a group of diabetic patients in main public hospitals in Damascus, Syria during the Syrian crisis - Ammar Hamzeh; Ghaith Almhanni; Yazen Aljaber; Rana Alhasan; Raneem Alhasan; MHD Imadaldin Alsamman; Nawras Alhalabi; Yousra Haddeh (BMC, 2019)
Abstract Background The awareness of diabetes mellitus (DM) and its complications, especially diabetic retinopathy (DR), is the key to reducing their burden. This study aimed to assess both the awareness of diabetic outpatients and their action towards periodic eye exam, and to determine the causes of non-compliance amongst patients who were aware. Because the Syrian Crisis affected all aspects of Syrians' life, the study aimed to determine the crisis' effects on patients' care-seeking behavior. Our study was the first step in paving the way of prevention strategies. Methods This observational cross-section study was conducted on 260 patients with DM who were visiting the four main hospitals in the Syrian capital, Damascus between August and November 2017. Results The mean (±SD) age of participants was 54.3(±12.8) years. Females were more than half (56.2%). The majority were from areas outside Damascus (72.3%). The mean (±SD) DM duration was 10.6 (±7.1) years. Almost all patients (93.8%) thought that DM could affect the eye. 67.3% believed that it could cause blindness. 86.9% of the patients conceived that DM patients should visit an ophthalmologist regularly. 37% did not visit any ophthalmologists at all, while 63% reported they had visited their ophthalmologists. Only 21.5% had a regular eye exam. Gender, educational level, economic status, province, and family history of DM had statistically an insignificant relation with an ophthalmologist visit. The preponderance of the patients who haven't visited regularly did not appreciate the necessity of regular eye exam. Diabetic neuropathy was the most common complication of DM that patients were aware of (92%) and suffered from (56.5%). Meanwhile, regarding the effects of the Syrian Crisis: 41.2% of diabetic patients had stopped their medications for at least one month, mainly because the drugs were unavailable (74.7% of them), as some drug companies had been destroyed. Half of the patients had struggled to reach a medical care center. Half of the patients had been displaced, two-third of them were from outside Damascus. Conclusion A screening program for DR should be initiated. Also, awareness about DM and its complications, especially DR, should be raised through doctors and media.